Pelatihan Pembuatan Surat untuk Kepala Dusun di Desa Sakra Selatan Kabupaten Lombok Timur - Safnowandi, Safnowandi; Sakti, Hadi Gunawan; Habiburrahman, Lalu; Rahmaniah, Ummu (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Village officials not only serve the community but must have innovations to develop the village in accordance with the demands of institutional change so that the village is able to compete with other villages. In other words, village officials must be able and observant in facing and taking advantage of various challenges and opportunities as a consequence of changing village institutions. Facing the desired conditions, the professionalism of village government apparatus resources is a must that cannot be postponed anymore. Because at this time village officials must have certain skills and knowledge, such as the demands of the village community for satisfactory services, which must be immediately responded to by the Village Government. Community services will be satisfactory if the administrative completeness of the village is complete. Training as an alternative for developing village apparatus resources needs to be carried out immediately as a consequence of changes in village government institutions and community demands for satisfactory services. To find out the needs needed by village officials in the context of developing village apparatus resources, it is necessary to identify the types and methods of training that are truly appropriate and no less important is the need for evaluation after the training. Departing from the explanation above, of course, the development of apparatus resources is directed so that village officials have the appropriate competencies needed to develop the region. The need for training is directed at meeting the needs of village officials, such as training in making letters for hamlet heads for administrative completeness, the end of which is the creation of satisfactory public services. This condition of limited human resource capabilities is currently also being felt by the Government in South Sakra Village. The goal to be achieved in this service activity is to carry out training and assistance for the South Sakra Village Apparatus, especially the hamlet head in the context of making letters to support their daily duties. The specific target to be achieved is to make South Sakra Village an Independent Village of Orderly Administration in East Lombok Regency. To achieve these specific goals and targets, the method used is the transfer of knowledge through the implementation of training and mentoring. Training activities will be devoted to training in making letters both manually and digitally. After the training is completed, the next step is to provide assistance to village officials related to the knowledge that has been obtained during the training.